Analysis of the Effects of Parameters on the Performance of Resonators Based on a ZnO/SiO2/Diamond Structure - Gang Cao; Hongliang Wang; Peng Zhang (Applied Sciences, 2024)
With the development of communications technology, surface acoustic wave (SAW) and bulk acoustic wave (BAW) devices have become hotspots of the competitive research in the frequency band above GHz. It imposes higher requirements on the operating frequency, temperature coefficient of frequency (TCF), and electromechanical coupling coefficient (k2) of SAW devices. In this work, we reported on a novel ZnO/SiO2/diamond-layered resonator structure and systematically investigated its propagation characteristics by using finite element methods. A comparative study and analysis of k2 and acoustic velocity (vp) for both the excited Rayleigh mode and the Sezawa mode were conducted. By selecting the appropriate ZnO piezoelectric film, SiO2, and electrode thickness, the Sezawa mode was chosen as the main mode, effectively improving both k2 and vp. It was observed that the k2 of the Sezawa mode is 7.5 times that of the excited Rayleigh mode and nearly 5 times that of piezoelectric single-crystal ZnO; vp is 1.7 times that of the excited Rayleigh mode and nearly 1.5 times that of piezoelectric single-crystal ZnO. Furthermore, the proposed multilayer structure achieves a TCF close to 0 while maintaining a substantial k2. In practical applications, increasing the thickness of SiO2 can compensate for the device’s TCF reduction caused by the interdigital transducer (IDT). Finally, this study explored the impact of increasing the aperture width and IDT pairs on the performance of the single-port resonator, revealing the changing patterns of quality factor (Q) values. The results reported here show that the structure has great promise for the fabrication of high-frequency and low-TCF SAW devices.